The Effects of Business Process Management on Improvement of Firm Performances - Kahrović, Ernad I; Krstić, Bojan D (Industrija, 2015)
The main purpose of this paper is to explore the acceptance of the business process orientation (BPO) in management practice of Serbian companies. The paper investigates the effects of business process management (BPM) on organizational performances. The empirical research was conducted on a sample of 120 enterprises by interviewing the managers, identifying their opinions and practices for the period 2012-2014. The research results demonstrate that the BPM elements have a positive influence on the performances of business processes. The obtained results are very useful for managers in Serbia, since they point out the relevance of more consistent application of business process management concept in day-to-day business activities with the aim of effective decision-making.